2020
DOI: 10.1088/2399-6528/abb322
|View full text |Cite
|
Sign up to set email alerts
|

Meat freshness revealed by visible to near-infrared spectroscopy and principal component analysis

Abstract: Increasing concerns about adulterated meat encouraged industry looking for new non-invasive methods for rapid accurate meat quality assessment. Main meat chromophores (myoglobin, oxy-myoglobin, fat, water, collagen) are characterized by close comparable absorption in visible to near-infrared (NIR) spectral region. Therefore, structural and compositional variations in meat may lead to relative differences in the absorption of light. Utilizing typical fiber-optic probes and integrating sphere, a degradation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The changes in total depolarization and scalar retardance spectra are displayed in Figure 2A and B are averaged over 800 × 600 pixels of corresponding images measured at different wavelengths. Apparently, the values of total depolarization and scalar retardance are increasing with the wavelength for both measurement time points, except for the dip at 550-nm wavelength which is attributed to the highest amount of myoglobin absorption 9,59 (Figure 2A). Higher concentration of myoglobin, which tend to have lower degree of scattering and birefringence.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The changes in total depolarization and scalar retardance spectra are displayed in Figure 2A and B are averaged over 800 × 600 pixels of corresponding images measured at different wavelengths. Apparently, the values of total depolarization and scalar retardance are increasing with the wavelength for both measurement time points, except for the dip at 550-nm wavelength which is attributed to the highest amount of myoglobin absorption 9,59 (Figure 2A). Higher concentration of myoglobin, which tend to have lower degree of scattering and birefringence.…”
Section: Resultsmentioning
confidence: 90%
“…When probing meat with polarized light, depolarization and rotation of the orientation of the polarization plane are dependent on the preferential orientation of the elongated muscle cells and meat aging. 7,8 Although there have been studies on meat freshness applying spectroscopic approaches, 9 the multiple scattering at visible and near-infrared wavelengths causes difficulties for quantitative tissue spectroscopy and imaging because of shallow penetration depth and the inhomogeneity of tissue which obscures the desired image information. 10 Hence, there is a growing interest to apply polarimetric imaging techniques for investigation of biomedical tissues because diffusely scattered light is often partially polarized to an extent, which can be experimentally, detected and carry additional nonredundant information on tissue optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle foods, including meat and fish, are very important from the point of view of human nutrition and commercial activity worldwide [151]. There have been significant efforts, both from the industry and academia, on improving quality and quantity of the raw and processed muscle food types in recent years [151][152][153][154][155]. Accordingly, there have been increasing demands for the development robust and time effective monitoring techniques to track compositional and safety compliance issues as conventional chemical methods of meat quality assessment become more expensive and time consuming.…”
Section: Nir Spectroscopy In Meat and Meat Products Fish And Seafoomentioning
confidence: 99%
“…Near infrared spectroscopy (NIR) has drawn considerable interest for many reasons, including its portability, speed, cost-effectiveness, suitability for in-line as well as on-line analysis, and the ability to concurrently measure different parameters for a large number of samples [151][152][153][154][155][156][157]. Several studies reported on the use of NIR for meat quality assessment and the analyses of meat properties in live animals or carcasses due to the capability of IR light to penetrate several layers of tissue [151][152][153][154][155][156][157][158][159]. Two published papers demonstrated that the short wavelength radiation in the NIR region of the electromagnetic spectrum can potentially be utilized to non-invasively assess meat quality [152,154].…”
Section: Nir Spectroscopy In Meat and Meat Products Fish And Seafoomentioning
confidence: 99%
See 1 more Smart Citation